2016
DOI: 10.1155/2016/8453462
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Aberrations, Contrast Sensitivity, and Light Distortion in Orthokeratology Patients: 1-Year Results

Abstract: Purpose. To evaluate the corneal higher-order aberrations (HOA), contrast sensitivity function (CSF), and light distortion (LD) in patients undergoing orthokeratology (OK). Methods. Twenty healthy subjects (mean age: 21.40 ± 8 years) with mean spherical equivalent refractive error M = −2.19 ± 0.97 D were evaluated at 1 day, 1 month, and 1 year after starting OK treatment. Monocular LD, photopic monocular CSF, and corneal HOA for 6 mm pupil size were measured. Results. LD showed an increase after the first nigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…While center-near MFCL induces large amounts of negative SA, center-distance MFCL induce an increase in positive SA [31,36]. Moreover, it has been reported that higher amounts of positive SA significantly increase LD, while a lower increase or even decrease can be found with negative SA [39][40][41]. On one level, this may explain the differences observed in LD between dominant (center-distance design) and non-dominant (center-near design).…”
Section: Discussionmentioning
confidence: 93%
“…While center-near MFCL induces large amounts of negative SA, center-distance MFCL induce an increase in positive SA [31,36]. Moreover, it has been reported that higher amounts of positive SA significantly increase LD, while a lower increase or even decrease can be found with negative SA [39][40][41]. On one level, this may explain the differences observed in LD between dominant (center-distance design) and non-dominant (center-near design).…”
Section: Discussionmentioning
confidence: 93%
“…Rah and his colleagues [ 23 ] showed that there was no difference in quality of life indices between refractive surgery and orthokeratology by using the National Eye Institute Refractive Error Quality of Life instrument (NEI-RQL 42). There are also a lot of studies hold that the overnight orthokeratology can induce significant changes in optical quality [ 8 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…[15,16,[18][19][20] A concern with OK lenses is loss of contrast; however, in this series contrast sensitivity (and visual acuity) did not deteriorate either in the OK group or the control group after lens wear. [22] A study by Tang et al measuring contrast sensitivity under both photopic and mesopic conditions corroborated this finding. [23] Corneal flattening by a mean of 1.2 D was observed by four months, with maximum flattening after initial overnight use.…”
Section: Discussionmentioning
confidence: 83%